Pengaruh Suku Bunga Dan Nilai Tukar Rupiah Terhadap Jumlah Uang Beredar di Indonesia Tahun 2023-2025 - Dewi, Nila Sari; Jayantika; Joice Lwisa Nababan; Ryan Chandra Dalimunthe (widya balina, 2026)
This study examines the influence of interest rates and the rupiah exchange rate on the money supply in Indonesia during the 2023–2025 period. A quantitative research approach was employed using monthly secondary data obtained from Statistics Indonesia (BPS) and Bank Indonesia (BI). The data were analyzed through multiple linear regression with the assistance of SPSS software. Several statistical procedures were applied, including classical assumption tests, partial significance tests (t-tests), simultaneous significance tests (F-tests), and coefficient of determination (R²) analysis. The findings reveal that interest rates have a significant negative effect on the money supply, while the rupiah exchange rate exerts a significant positive influence. Furthermore, the simultaneous test indicates that both variables collectively have a significant impact on the money supply. The coefficient of determination shows that 85.4% of the variation in the money supply can be explained by changes in interest rates and the rupiah exchange rate. These results highlight the importance of maintaining stable interest rates and exchange rates as essential components of monetary policy aimed at regulating the money supply and preserving monetary stability in Indonesia.